Cytogenetic Mapping of the Retroelements Rex1, Rex3 and Rex6 among Cichlid Fish: New Insights on the Chromosomal Distribution of Transposable Elements - Valente, G. T. [UNESP]; Mazzuchelli, J. [UNESP]; Ferreira, I. A. [UNESP]; Poletto, A. B. [UNESP]; Fantinatti, B. E. A. [UNESP]; Martins, C. [UNESP] (Karger, 2011)
To enhance our understanding of the organization of the genome and chromosome evolution of cichlid fish species, we have isolated and physically mapped onto the chromosomes the transposable elements (TEs) Rex1, Rex3 and Rex6, which are conserved in teleost fish, in the chromosomes of African and South American cichlid species. The physical mapping of different Rex elements showed that they are primarily compartmentalized in the pericentromeric heterochromatic regions, although dispersed or clustered signals in euchromatic regions were also observed. The presence of TEs in heterochromatin can be correlated with their role in the structure and organization of heterochromatic areas (such as centromeres) or with the lower selective pressure that act on these gene-poor regions. The Rex elements were also concentrated in the largest chromosome pair of the Nile tilapia, Oreochromis niloticus. This chromosome pair is supposed to have originated by fusions, demonstrating the possible involvement of TEs with chromosome rearrangements. Besides general patterns of chromosomal distribution, comparative analysis suggests that Rex elements could differ in their chromosomal distribution among different fish groups or species and that intrinsic aspects of the genomes could influence the spread, accumulation or elimination of TEs. Copyright (C) 2010 S. Karger AG, Basel
Keywords: Chromosome evolution; Genome evolution; Transposable elements